Introduction to Working with Manuscripts for Medievalists - Bak, János M. (Gorgias Handbooks, 2017)
A short guide for studying, editing and translating medieval texts in manuscript form, outlining the technical steps for preparing a medieval manuscript for print: evaluating and describing the manuscript itself (transmission, provenance, and physical description), textual criticism (reconstruction, emendation, authenticity, dating, and authorship), and steps to preparing an edition or translation.